Increasing The Adaptive Capacity of Fishermen: Analysing The Role of Livelihood Capital in Building Resilience of Small-Scale Fisheries in The South Coast of East Java, Indonesia (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
Small-scale fisheries are an important sector that contributes to increasing food security, alleviating poverty, and escalating employment opportunities. However, the magnitude of this contribution is not in line with the condition of small-scale fishermen who are still trapped in marginal and underdeveloped conditions and depend on natural resources to fulfill their daily lives. Climatic, social, economic, and technological variability also pressures fishermen's lives. Structural burdens, marginalization, and underdevelopment can make fishermen vulnerable to change and unexpected events. This research uses SEM-PLS to simultaneously test the influence of livelihood capital on the adaptive capacity of small-scale fishermen. The results show that spatial properties have the greatest influence to technological capital. Psychological capital has been proven to be the strongest factor that directly increases adaptive capacity. Furthermore, human capital acts as a key mediator linking the influence of spatial properties on adaptive capacity. This finding emphasizes that improvements in spatial properties supported by human capital can encourage the use of technology and psychological resilience, thereby increasing fishermen’s adaptive capacity. The results of this study have implications for enriching the literature on the implementation and exploration of multidimensional livelihood capital held by fishermen in coastal areas to achieve sustainable livelihoods for fishermen in developing countries.